A COMPLEX OF ART FORMS USED IN SHAPING THE ARTISTIC IMAGE OF THE URBAN ENVIRONMENT: SCULPTURE AND THREE-DIMENSIONAL COMPOSITIONS (BASED ON THE CITY OF NAMANGAN) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article analyzes the role of sculpture and three-dimensional compositions in shaping the artistic image of the urban environment. The study is conducted using the city of Namangan as a case study, specifically analyzing the artistic and spatial organization of Chorsu Square. The research methodology is based on visual analysis, field observations, and a comparison of historical and contemporary urban environments. The results demonstrate that the lack of artistic elements in modern areas reduces the aesthetic quality and social appeal of the environment. The article proposes a conceptual model for the development of public spaces based on interactive art objects.